Sistem Informasi Manajemen Rusunawa Politeknik Negeri Bengkalis Menggunakan Metode Scrum - Sofia Randa; Muhammad Asep Subandri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on the development of a multiplatform management information system for Rusunawa (student dormitory) at Politeknik Negeri Bengkalis to address inefficiencies in the current manual system, which relies on Google Forms for registration and Microsoft Excel for resident data management. The existing approach presents several limitations, including slow data processing, difficulties in tracking and monitoring rental payments, and limited transparency in administrative processes. These issues often lead to delays, errors, and reduced satisfaction among both residents and administrators. To overcome these challenges, the proposed system was developed using the Scrum methodology, an agile software development framework known for its iterative, adaptive, and user-centered approach. The Scrum process allowed continuous feedback from stakeholders and regular refinement of system features to align with evolving needs. Key functionalities integrated into the system include resident registration, room rental management, centralized resident data storage, online payment processing, facility complaint submissions, and an automated notification system for both administrators and residents.and evaluation of the system demonstrate significant improvements in operational efficiency. The digital platform enables faster and more accurate processing of resident registrations and room rentals, as well as real-time tracking of payments. The online payment feature reduces manual transaction errors and facilitates timely payment confirmation. The facility complaint module ensures better communication between residents and management, while the notification system provides timely updates to all parties. Overall, the implementation of this information system enhances transparency, minimizes administrative workload, and improves service quality. Students benefit from an easier, faster, and more accessible process for renting rooms and making payments, while administrators gain a structured and efficient tool for data management and operational monitoring. This study highlights the potential of agile-based digital solutions to transform traditional administrative systems in higher education housing management.